Al-Qur'an and Multicultural Education: From Text to Social Action - Muhammad Aji Nugroho (Didaktika Religia, 2021)
The social crisis in society occurs because the process of social interaction is still fragile regarding the awareness of pluralism and multiculturalism which results in weak social solidarity. Ideally, the issue ends with religious doctrine, which teaches peace and brotherhood with mutual respect. However, this value is lost by an improper understanding of the Qur’an. This study aims to describe and critically analyze multicultural education in the Qur’an as a process of understanding and practicing Islamic teachings in a fair, balanced, and moderate manner. The design of this research is library research whose main object is the Qur’an using the thematic method (mauḍūī), and emancipatory critical hermeneutics as a tool for interpreting and processing text. The results show that Islam is a religion that always advocates harmonization, and hates violence and hypocrisy. The concept of Islam other than monotheism is justice, independence, and freedom. The Prophet was sent to uphold justice because justice is universal. Four freedoms for humans in the Qur’an, are freedom to live, freedom of religion, freedom of ownership, and self-esteem. Pluralism is not only the will of God but also the will of history. Everything is intended so that humans compete in the pursuit of goodness, growing a healthy shared attitude by recognizing each other’s potential, realizing benefits by covering shortcomings, which shows that all humans are equal in the diversity that exists. So that there is no domination of the minority over the majority and an attitude of mutual help grows.